2021
DOI: 10.1002/admi.202100907
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐Step Chemical Solution Deposition‐Annealing Process Toward Wake‐Up Free Ferroelectricity in Y:HfO2 Films

Abstract: Ferroelectricity in HfO2 thin films can be utilized for fast, power‐efficient, and highly scalable non‐volatile memories. However, the required wake‐up process for inducing ferroelectricity/ achieving higher polarization is one of the major hurdles that hinder HfO2‐based thin films from developing reliable electronic devices. The wake‐up effect is believed to originate from i) phase transformation from non‐ferroelectric to ferroelectric, ii) movement of defect entities (mainly oxygen vacancy defects) near the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…As presented in our previous report, the microstructure observed is very uniform without any cracks, pores, or other kinds of discontinuities. 24 Therefore, a sharp transition is expected – evident from the transition shown in Fig. 2(b).…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…As presented in our previous report, the microstructure observed is very uniform without any cracks, pores, or other kinds of discontinuities. 24 Therefore, a sharp transition is expected – evident from the transition shown in Fig. 2(b).…”
Section: Resultsmentioning
confidence: 91%
“…The large polarization is the outcome of Y-doping at a suitable concentration. 24 According to the comparative study reported by Starschich et al , polarization strongly depends on the ionic size of the dopants, and an ionic radius of around 85 pm is suitable for achieving a high P r . 34 Thus, rare earth elements such as La, Y, Nd, Sm, and Er are suitable to achieve large polarization.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations